IDENTIFIKASI POTENSI SUMBER AIR PANAS DALAM PEMANFAATAN THERMO ELECRIC GENERATOR (TEG) DENGAN MENGGUNAKAN THERMOCOUPLE TYPE-K - Rifaldo Pido (Gorontalo Journal of Infrastructure and Science Engineering, 2020)
Hot springs are springs that are generated as a result of the discharge of groundwater from the earth's crust after being heated geothermally. This geological condition contributes significantly to the availability of geothermal energy in Indonesia, especially geothermal energy in Pentadio Village, Gorontalo District, this geothermal energy is one of the tourism objects in Gorontalo Regency, based on the results of field studies that in measuring temperature for several the measurement point which is located at a point distance of 60 cm x 60 cm. Temperature measurements were carried out at the bottom and top 4 points with an internal distance between the bottom point and the top point of 60 cm, a depth of 1.5 m with an area of 2x3 m2. From the results of the measurement of water temperature for the lower temperature (TB) is at a depth of 140 cm, while the measurement of the water temperature for the upper temperature (TA) is at a depth of 145.5 cm from the total depth of hot springs 150 cm. nine hours per day and the results of these measurements show a difference. The highest average value for lower temperature (TB) at a depth of 140 cm is 90oC, while the highest average value for upper temperature (TA) at a depth of 145.5 cm is 87.75 oC Sumber air panas adalah mata air yang dihasilkan akibat keluarnya air tanah dari kerak bumi setelah dipanaskan secara geothermal. Kondisi geologi ini memberikan kontribusi nyata akan ketersediaan energi panas bumi di Indonesia khususnya energi panas bumi yang ada di Desa Pentadio Kabupaten Gorontalo, energi panas bumi ini merupakan salah satu objek pariwisata yang ada di Kabupaten Gorontalo, berdasarkan hasil studi lapangan bahwa dalam pengukuran temperatur untuk beberapa titik pengukuran yang berada lokasi dengan jarak titik yaitu 60 cm x 60 cm. Pengukuran temperatur dilakukan di 4 titik bagian bawah dan atas dengan inteval jarak antara titik bawah dan titik atas 60 cm kedalaman 1,5 m dengan luas area 2x3 m2. Dari hasil pengukuran suhu air untuk temperatur bawah (TB) berada pada kedalaman 140 cm, sedangkan pengukuran suhu air untuk temperatur atas (TA)  berada pada kedalaman 145,5 cm dari total kedalaman sumber air panas 150 cm, pengukuran dilakukan selama empat hari dan selama sembilan jam per hari dan dari hasil pengukuran tersebut menunjukan adanya perbedaan. Nilai tertinggi rata-rata untuk temperatur bawah (TB)  pada kedalaman 140 cm adalah 90oC, sedangkan  Nilai tertinggi rata-rata untuk temperatur atas (TA) pada kedalaman 145,5 cm adalah 87,75 oC